2023
DOI: 10.1186/s12575-023-00195-1
|View full text |Cite
|
Sign up to set email alerts
|

YTHDF2 exerts tumor-suppressor roles in gastric cancer via up-regulating PPP2CA independently of m6A modification

Abstract: Background YTHDF2 is one of important readers of N6-methyladenosine (m6A) modification on RNA. Growing evidence implicates that YTHDF2 takes an indispensable part in the regulation of tumorigenesis and metastasis in different cancers, but its biological functions and underlying mechanisms remain elusive in gastric cancer (GC). Aim To investigate the clinical relevance and biological function of YTHDF2 in GC. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…During recent decades, a massive number of studies have revealed that YTHDF2 destabilizes m6A-containing RNA, [9][10][11] and studies also have reported that there are m6A sites in AURKB mRNA. 39,40 Our results showed that the knockdown of METTL3 led to a downregulation of m6A modification in AURKB, which may subsequently inhibit the decay of AURKB mRNA in an m6A-YT-HDF2-dependent manner within goat granulosa cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During recent decades, a massive number of studies have revealed that YTHDF2 destabilizes m6A-containing RNA, [9][10][11] and studies also have reported that there are m6A sites in AURKB mRNA. 39,40 Our results showed that the knockdown of METTL3 led to a downregulation of m6A modification in AURKB, which may subsequently inhibit the decay of AURKB mRNA in an m6A-YT-HDF2-dependent manner within goat granulosa cells.…”
Section: Discussionmentioning
confidence: 99%
“…The core components of writers include methyltransferase‐like 3 (METTL3), METTL14, and Wilms tumor 1 associated protein (WTAP), while examples of erasers in mammals include alkB homolog 5 (ALKBH5) and fat mass and obesity‐associated protein (FTO). YTH N6‐Methyladenosine RNA Binding Protein 2 (YTHDF2) is one of the m6A “readers” that decodes the m6A mark and mediates RNA decay along with other proteins 9–11 . While many studies have reported on the functions of m6A in ovary development, 6,12–14 the mechanism by which m6A participates in oocyte maturation through granulosa cells in mammals, especially domestic animals, has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…YTHDF2 is a noteworthy reader protein that has been proven to be overexpressed in GC tissues and cell lines and involved in gastric carcinogenesis by regulating mRNA metabolism and translation. Functionally speaking, YTHDF2 knockdown could dramatically inhibit the proliferation, migration, and invasion of GC cells 27 . But the mechanism of the tumor‐promoting mechanism of YTHDF2 remains inconclusive.…”
Section: Synergisms In Jak1 Mrna Metabolic Process: Linc00659 and Ythdf2mentioning
confidence: 99%
“…Functionally speaking, YTHDF2 knockdown could dramatically inhibit the proliferation, migration, and invasion of GC cells. 27 But the mechanism of the tumorpromoting mechanism of YTHDF2 remains inconclusive. In Fang's work, LINC00659 was found responsible for the formation of the ALKBH5 complex, which is required for the binding with JAK1 mRNA.…”
Section: Synergisms In Jak1 Mrna Metabolic Process: Linc00659 and Ythdf2mentioning
confidence: 99%